PENGEMBANGAN BAHAN AJAR BERBASIS BUDAYA LOKAL KALBAR PADA PEMBELAJARAN IPAS KELAS IV SDN 39 PONTIANAK KOTA - Ayu, Tresia; Hamdani, Hamdani; Pranata, Rio (Universitas Tanjungpura, 2024)
This development research aims to determine the process of developing teaching material products based on local culture in West Kalimantan in class IV SDN 39. This research uses the Research and Development (RnD) method using the ADDIE model. The data sources in this research were the homeroom teacher, 32 class IVB students and 2 expert validators. Data collection techniques in this research are observation, interviews and questionnaires. The development of local culture-based teaching materials adopts three research steps, namely analysis, design and development. At the analysis stage, the researcher carried out a needs and curriculum analysis. The next step taken at the design stage is to determine learning indicators and design teaching materials. The research results obtained at the development stage were that the teaching material product developed was very suitable for use in terms of the level of validity and practicality of the teaching material. The level of validity of the local culture-based teaching material development product obtained a score of 4.4 with the criteria